IMPLEMENTASI LANDASAN SOSIOLOGIS PENGEMBANGAN KURIKULUM DALAM MENINGKATKAN MINAT PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Harun (Ilma Jurnal Pendidikan Islam, 2023)
Abstract Education is an effort to develop the potential that exists in a person, to achieve the desired goals. Education in an Islamic perspective is the teaching that God gave to humans in the form of the Qur'an. In education, it contains what is called a curriculum, in general the curriculum is a design that contains a set of subjects and/or material that will be studied or will be taught by educators to students. In this study using the library research research method. In this study, library research was used, in which research was conducted using sources as exploratory media, such as books, books, works of logic, notes or past exam reports and exam results. The results of this study show that the sociological basis for curriculum development must actually be built and developed while still referring to social principles and community needs. Through the sociological foundation of curriculum development, the role of education can be prepared in increasing interest in learning Islamic religious education. The development of an Islamic religious education curriculum can be interpreted in three perspectives, activities that produce an Islamic religious education curriculum, processes that link one component with other components to produce a better Islamic religious education curriculum, and/or design, implementation, assessment activities. , and improvement of Islamic religious education curriculum. Keywords: Sociological Basis, Curriculum Development, Interest in Learning PAI